Islamic Banking Innovation and Customer Satisfaction: A Case Study of Indonesia and Nigeria - Yarmanti A., Violla; Wissalam Bustami, Alek; Muhammad Ardo, Adam (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose - The study examined the impact of digital accessibility, transparency, security, and product innovation on consumer trust and engagement. Method - This study utilized a qualitative research methodology, incorporating in-depth interviews and thematic analysis to extract insights from Islamic banking clients and industry specialists. The data gathering emphasized consumer experiences, opinions of service quality, and expectations for digital financial services. Findings - The results demonstrated that users of Islamic banking prioritize service quality, security protocols, and digital accessibility. Customers demonstrate a pronounced inclination towards mobile banking services that incorporate sophisticated yet intuitive features, as well as more transparency in financial transactions and investment methodologies. Moreover, proficient risk management and the use of fintech technologies enhanced client trust and happiness. Practical Implications - The study advances consumer behavior theories in Islamic banking by linking technology adoption, institutional trust, and Shariah compliance. It calls for Islamic banks to invest in advanced digital security, enhance financial transparency, and innovate Shariah-compliant products in line with SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure) Originality/value - an innovative, comprehensive analysis of the convergence of Islamic banking services, technological progress, and consumer expectations by incorporating numerous variables, including security, transparency, and innovation, into a coherent framework